Electroclinical features of MEF2C haploinsufficiency-related epilepsy: A multicenter European study. (May 2021) - Raviglione, Federico; Douzgou, Sofia; Scala, Marcello; Mingarelli, Alessia; D'Arrigo, Stefano; Freri, Elena; Darra, Francesca; Giglio, Sabrina; Bonaglia, Maria C; Pantaleoni, Chiara; Mastrangelo, Massimo; Epifanio, Roberta; et al.
Highlights: Epilepsy is common in MEF2C syndrome (80% of cases), typically within 3 years of life. About 50% of patients have febrile seizures and epilepsy featuring 2 seizure types. More than a third of subjects show myoclonic seizures since disease onset. Typical interictal EEG shows paroxysmal hypersynchronous discharges in frontal regions. Myoclonic seizures and spasms are associated with ADGRV1, MIR9-2, and LINC00461 haploinsufficiency. Abstract: Purpose: Epilepsy is a main manifestation in the autosomal dominant mental retardation syndrome caused by heterozygous variants in MEF2C . We aimed to delineate the electro-clinical features and refine the genotype-phenotype correlations in patients with MEF2C haploinsufficiency. Methods: We thoroughly investigated 25 patients with genetically confirmed MEF2C -syndrome across 12 different European Genetics and Epilepsy Centers, focusing on the epileptic phenotype. Clinical features (seizure types, onset, evolution, and response to therapy), EEG recordings during waking/sleep, and neuroimaging findings were analyzed. We also performed a detailed literature review using the terms "MEF2C", "seizures", and "epilepsy". Results: Epilepsy was diagnosed in 19 out of 25 (~80%) subjects, with age at onset <30 months. Ten individuals (40%) presented with febrile seizures and myoclonic seizures occurred in ~50% of patients. Epileptiform abnormalities were observed in 20/25 patients (80%) and hypoplasia/partial agenesis of the corpus callosum was detected in 12/25 patients (~50%). Nine patients harbored a 5q14.3 deletion encompassing MEF2C and at least one other gene. In 7 out of 10 patients with myoclonic seizures, MIR9-2 and LINC00461 were also deleted, whereas ADGRV1 was involved in 3/4 patients with spasms. Conclusion: The epileptic phenotype of MEF2C -syndrome is variable. Febrile and myoclonic seizures are the most frequent, usually associated with a slowing of the background activity and irregular diffuse discharges of frontally dominant, symmetric or asymmetric, slow theta waves with interposed spike-and-waves complexes. The haploinsufficiency of ADGRV1, MIR9-2, and LINC00461 likely contributes to myoclonic seizures and spasms in patients with MEF2C syndrome.